KORELASI PENERAPAN PRINSIP-PRINSIP CORPORATE GOVERNANCE DENGAN MANAJEMEN LABA - Maya Indriastuti (Jurnal Ekonomi dan Bisnis, 2014)
This study was conducted to analyze the correlation between the application of the principles of corporate governance (fairness, transparency, accountability, and responsibility) with earnings management in companies listed on the Indonesia Stock Exchange in 2011-2012 and gives an overview of how the implementation of corporate governanceini can reduce management actions profits made by the company manager. This study used secondary data from publicly traded companies nonlembagakeuangan ever survey of corporate governance followed PerceptionIndex 2009 to 2012 conducted by The IndonesianInstitute for Corporate Governance(IICG). Tests carried out using correlation test. Tests conducted for 2011-2012 and combined in 2011 and 2012. Wherewith Test results show that in general, the application of the principles of governance goodcorporate not guarantee the absence of earnings management yangdilakukan by the company. .Keywords: agency theory, earnings management, corporate governance, corporate nonfinancial institutions, and correlation test